P Pelatihan Pembuatan Plant Growth Promoting Rhizobacteria dari Akar Bambu pada Kegiatan KKN di Desa Jejangkit Pasar : Training of Making Plant Growth Promoting Rhizobacteria from Bamboo Roots on KKN Activities in Jejangkit Pasar Village - Andini, Yulia; Persada, Maulida Bintang; Yuliani, Novi Dwi; Busyiri, Muhammad; Lela, Nor; Ramadhani, Ansari; Indrimaya, Tiara Divani; Jumiyati, Jumiyati; Sahrudin, Sahrudin; Syifa, Herda Aulia Lailatul; Sutrianto, Sutrianto (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
Kuliah Kerja Nyata (KKN) is a form of implementation of the Tri Dharma of Universitas Nahdlatul Ulama Kalimantan Selatan, which is located in Jejangkit Pasar Village, Barito Kuala Regency, South Kalimantan Province. People's livelihoods are dominated by the agricultural sector. In this regard, observations made found that most farmers use non-organic fertilizers on agricultural land, either purchased independently or in the form of subsidies provided by the government. Meanwhile, based on the results of interviews with representatives of farmer groups, it was revealed that the level of need of farmers in Jejangkit Pasar Village for non-organic fertilizers is very high, while farmers' knowledge about the impact of non-organic fertilizers is still low, especially on the environment. So it is necessary to provide provisions to farmers in Jejangkit Pasar Village so that they can transition from using non-organic fertilizers to organic fertilizers. Through KKN activities, the 10 UNUKASE 2024 KKN groups carried out training and direct practice in making Plant Growth Promoting Rhizobacteria (PGPR) from bamboo roots carried out by resource persons from the Jejangkit Agricultural Extension Center (BPP). As a result, all the farmers who attended understood how to make PGPR from bamboo roots and as many as 71.42% of the farmers who attended stated that they wanted to apply PGPR fertilizer to their agriculture.